HBR's 10 must reads on strategy. - Harvard Business Review (Harvard Business Review Press, 2011)
HBR's 10 Must Reads on Strategy will inspire you to:Distinguish your company from rivals. Clarify what your company will and won't do. Craft a vision for an uncertain future. Create blue oceans of uncontested market space. Use the Balanced Scorecard to measure your strategy. Capture your strategy in a memorable phrase. Make priorities explicit. Allocate resources early. Clarify decision rights for faster decision making